Microwave-Assisted Synthesis Method for the Production of Carbon Nano Dots and Its Genotoxicity Assessment - Tekin, Zeynep; Ergenler, Aysegul; Zaman, Buse Tugba; Tahir Gunkara, Omer; Depci, Tolga; Turan, Funda; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2024)
In this study, nitrogen-doped carbon nanodots (N-CNDs) were synthesized from Citrus reticulata using microwave-assisted process and material's genotoxic effects were investigated in Daphnia magna. Morphological size and shape variations of the synthesized N-CNDs were evaluated by using zetasizer and transmission electron microscope. Acute/chronic toxicity experiments were performed using method by OECD (Organization for Economic Cooperation and Development) 202-212 guidelines. Daphnia magna was subjected to the N-CNDs produced from Citrus reticulata at the different concentrations ranging between 0.04 and0.24 mg tangerine equivalent N-CND/mL for 96 h at 20 degrees C. After 96 h, the LC50 (lethal concentration- at which 50% of cells) value of N-CNDs was determined to be 0.1 mg equivalent N-CND/mL using probit analysis. Based on toxicity levels determined by EU-Directive 93/67/EEC, N-CNDs are classified in the nontoxic category. The toxicological assessments of sublethal concentrations of N-CNDs demonstrated that 0.013 mg tangerine equivalent N-CND/mL dose group exhibited a similar profile to the control group, indicating its safety. Although the DNA damage frequency of the 0.03 and 0.06 mg equivalent N-CND/mL dose groups was found to be higher than control group, these levels were observed almost 70% lower than the DNA damage frequency found in the mutagenic group/positive group.
Keywords: Carbon nanodots; Citrus reticulata; Daphnia magna; Model organism; Nanotoxicology; GREEN SYNTHESIS; DNA-DAMAGE; NANOPARTICLES; TOXICITY; Chemistry